Avaliação de crescimento, produção de biomassa e produção de óleo essencial na cultura da Melissa officinalis L. cultivada em casa de vegetação e submetida a diferentes regimes hídricos - Caldas, André Luiz Dias (2019)
Given the importance of growing Melissa officinalis L. and the favorable outlook for natural product market growth, it is of utmost importance to develop studies that increase efficiency and optimize the use of inputs to maximize crop production and profitability of the producer. The objective of this work was to evaluate the influence of soil water availability, in relation to the replacement volume (experiment I) and irrigation frequency (experiment II), on growth, biomass production, yield and yield of essential oil in the culture of Melissa officinalis L. grown in a greenhouse and in two growing seasons (summer and spring). The experiments were carried out in a greenhouse on the campus of the Federal University of Lavras, Lavras, MG. The experimental design was a randomized complete block with 5 treatments (experiment I) and 5 treatments (experiment II), 4 replicates per treatment and 6 plants per replicate (5x4x6), in both experiments. In the experiment I the treatments consisted of five volumes of water replenishment, defined by 25%, 75%, 100%, 125% and 150% of the volume evapotranspirated by the crop (ETc). In the experiment II, the irrigation frequency was evaluated, with treatments of 2, 3, 4, 5 and 6 days, and 100% recovery of ETc accumulated in these periods. The evaluated characteristics were: plant height, stem diameter, leaf dry biomass, root dry biomass, shoot / root ratio, leaf area, yield and yield of essential oil and water productivity in relation to dry biomass production in relation to the production of essential oil. The results showed that the availability of water in the soil did not affect growth in height and diameter, nor did it affect the yield of essential oil. However, biomass production, essential oil production and water productivity are affected by the availability of water in the soil, that is, with an increase in the replacement volume and an increase in the irrigation frequency, there was an increase in biomass production values and essential oil production and decrease in water productivity values.